Henry Kissinger papers - Kissinger, Henry, 1923-
Correspondence, memoranda, telegrams, cables, memoranda of conversations, typewritten transcripts of telephone conversations ("telcons"), minutes of meetings, interviews, articles, speeches, reports, agenda and briefing papers, talking points, research and policy papers, notes, biographical material, press releases, printed material, maps, audiotapes, and other papers relating chiefly to Kissinger's service as assistant to the president for national security affairs, 1969-1975, and as secretary of state, 1973-1977, in the administrations of presidents Richard M. Nixon and Gerald R. Ford.
Subjects include the Vietnamese conflict, rapprochement with China and a triangular global balance between East and West, reduction of U.S.-Soviet tensions through arms control talks and detente, and the search for peace in the Middle East. Includes papers pertaining to Kissinger's July 1971 trip to China, the strategic arms limitation treaty (SALT), Anatoliy Fedorovich Dobrynin, Andrei Andreevich Gromyko, and the October 1973 Middle East war.
Photocopies of the telcons (1969-1976) produced from originals in the Manuscript Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Division.
U.S. secretary of state. Full name: Henry Alfred Kissinger.
Keywords: Dobrynin, Anatoly, -- 1919-2010.; Ford, Gerald R., -- 1913-2006.; Gromyko, Andreĭ Andreevich, -- 1909-1989.; Nixon, Richard M. -- 1913-1994.; Soviet Union. -- 1972 May 26 (SALT); United States. -- Assistant to the President for National Security Affairs; United States. -- Department of State; Arms control; Arab-Israeli conflict; Arab-Israeli conflict -- 1973-1993.; Detente; International relations; National security -- United States; Peace; Vietnam War, 1961-1975.; China -- Foreign relations -- United States; Middle East -- History -- 20th century; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- China; United States -- Foreign relations -- Soviet Union; United States -- Politics and government -- 1969-1974.; United States -- Politics and government -- 1974-1977.; Vietnam -- History -- 1945-1975.; Cabinet officers